Real-world experience and prognostic factors in ovarian carcinosarcoma: a single-center retrospective study from China - Ji, Wanwan; Zhuo, Yunmei; Cheng, Xianzhong (Frontiers in Oncology, 2025)
ObjectiveOvarian carcinosarcomas (OCS) is a rare type of ovarian cancer. Due to its low incidence, studies are limited to several case reports/case series and small-scale retrospective study. We carried out this study to explore prognostic factors and treatment strategies for OCS.MethodsPatients diagnosed with OCS between March 2012 and October 2023 at Jiangsu Cancer Center were enrolled in this study. Baseline Characteristics, treatment strategies and survival of all enrolled patients were recorded. Kaplan-Meier analysis with a log-rank Mantel-Cox test was used to compare progression-free survival (PFS) between different groups.ResultsTwenty-six patients met inclusion criteria. The median PFS of all enrolled patients was 17.53 months. We firstly demonstrated that patients with ascites ≥500 ml (27.83 months vs. 13.7 months, p=0.12, HR 0.72), age ≥58 years (22.93 months vs. 13.53 months, p=0.354, HR 0.62), diameter of tumor<10cm (27.83 months vs. 12.80 months, p=0.095, HR 0.36), Ki-67 ≥70% (22.93 months vs. 13.53 months, p=0.093, HR 0.39) had a trend of better prognosis. Five patients underwent genetic testing, 4 of whom were homologous recombination deficiency (HRD)-positive and treated with PARP inhibitor (PARPi). The median PFS of the 4 patients was 22.68 months.ConclusionsOur study demonstrated that age at diagnosis, diameter of tumor, Ki-67 index, and volume of ascites may be prognostic factors of OCS. Patients with HRD positive/BReast CAncer gene (BRCA) mutation may benefit from PARPi.